2023
DOI: 10.3389/fpubh.2023.987418
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to earthquake preparedness of households based on social-cognitive theory constructs: A systematic review

Abstract: BackgroundEarthquakes cause many casualties worldwide. Taking preventive measures and improving community preparedness is critical to reducing earthquake damage. The social cognitive theory explains how individual and environmental factors cause behavior. This review was conducted to identify the social cognitive theory structures, in research on the preparedness of households against earthquakes.Materials and methodsThis systematic review was performed based on the Preferred Reporting Items for Systematic Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…The results of a systematic review study showed that people with higher self-efficacy took more preventive measures against disasters and had more preparedness intentions and behavior ( 38 ). In the Cong study in the United States, low self-efficacy and response efficiency were reported as barriers to household preparedness against disasters ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of a systematic review study showed that people with higher self-efficacy took more preventive measures against disasters and had more preparedness intentions and behavior ( 38 ). In the Cong study in the United States, low self-efficacy and response efficiency were reported as barriers to household preparedness against disasters ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Son varios los aspectos clave que nos obligan a hacer una profunda reflexión sobre la ayuda de emergencia en desastres. Por un lado, un factor fundamental es disminuir la vulnerabilidad de la población y mejorar la preparación del sistema en su globalidad, tanto a nivel sanitario, logístico, de protección civil y educación de la población 19,20 . En ocasiones, por muy bien preparado que este un país, éste hace un llamamiento de ayuda internacional, que permite la entrada al país de equipos internacionales.…”
Section: Aspectos Claveunclassified
“…American public health agencies work to help people respond to disasters and emergencies. In 2003, the U.S. Federal Emergency Management Agency launched a national emergency preparedness campaign to encourage the public to prepare emergency supplies [4]. In Australia, approximately one-fth of households have mobile phones, rst-aid kits, batteries, and other rst-aid items [5].…”
Section: Introductionmentioning
confidence: 99%